Aspirin versus clopidogrel after surgical offpump coronary revascularization – a prospective, randomized, head-to-head pilot trial - Suwalski, Grzegorz; Banach, Magdalena; Smoczyński, Radosław; Mróz, Jakub; Gryszko, Leszek; Szałański, Przemysław; Krawczyk, Karol; Hendzel, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: Postoperative clopidogrel use after surgical coronary revascularization may provide short- and long-term reduction of risk of negative cardiovascular events. However, there are not enough data from prospective randomized trials comparing head-to-head monotherapy with either aspirin or clopidogrel. Aim of the study: The aim of the study was to evaluate the safety and effectiveness of aspirin or clopidogrel use in patients after elective coronary artery bypass grafting. Material and methods : The study involved 50 patients who were referred for elective off-pump coronary artery bypass grafting (OPCAB). Preoperatively patients were randomized to postoperative antiplatelet treatment with either aspirin (150 mg per day) or clopidogrel for 6 months (75 mg per day). After 6 months all patients were turned to aspirin. In all patients platelet function on aspirin was checked before surgery. After 1, 6 and 12 months in all cases follow-up was collected in terms of any adverse events. Results : During follow-up 26 negative events occurred, including repeated revascularization, stroke and bleeding. In the clopidogrel arm cumulative risk of negative events was significantly lower (14%) in comparison to the aspirin group (25%, p < 0.05). In patients with preoperative persistent platelet function on aspirin the highest cumulative event risk was observed (35%). The lowest cumulative event risk was observed in aspirin responders randomized to the clopidogrel arm (2%).  Conclusions : Clopidogrel therapy provided for 6 months after OPCAB instead of the standard aspirin protocol may reduce the risk of negative adverse cardiovascular events. Occurrence of preoperative persistent platelet function on aspirin is related to worse 1-year outcome after off-pump coronary revascularization.